Pengaruh Profitabilitas, Leverage, Ukuran Perusahaan dan Nilai Pasar Terhadap Carbon Emission Disclosure pada Perusahaan Sektor Energi yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2023 - Adillah, Adillah; Maryati, Ulfi; Afni, Zalida (Jurnal Eksplorasi Akuntansi, 2025)
The goal of this study is to examine how carbon emission disclosure is impacted by profitability, leverage, company size, and market value. This study was carried out using an associative approach and quantitative methods. The Indonesia Stock Exchange's sustainability and annual reports, as well as the websites of individual companies, provided the data for this study. The study's sample comprised 21 companies from the energy sector that were listed on the Indonesia Stock Exchange (IDX) between 2019 and 2023. Multiple linear regression analysis served as the primary analysis technique to test the hypothesis, and the sample selection process was founded on the purposive sampling method. The results of this study show partially that profitability, company size and market value have a positive effect on carbon emission disclosure. Meanwhile, leverage has no effect on carbon emission disclosure.